Phase equilibrium liquid-vapor in three-component system UF6-IF5-BrF3 at complete mutual components solubility - Zherin (Gerin) I. I. Ivan Ignatyevich; Usov V. F.; Ostvald R. V. Roman Vyacheslavovich; Shagalov V. V. Vladimir Vladimirovich; Gayday I. V.; Tyulyubaev Z. M. (Chemistry, 2007)
Заглавие с титульного листа